CT Guided Stereotactic Brain Tumor Biopsy (Bangladesh Journal of Neurosurgery, 2020)
153 cases of CT guided stereotactic biopsies for intra-axial deep seated brain lesions performed by one neurosurgeon has been analyzed regarding procedure, success rate and complications. Of the 153 cases, positive tissue biopsy was found in 143 cases. In 6 patients, biopsy showed gliotic grain tissue or normal brain tissue.4 patients had complications after the procedure. Three patient developed intracerebral haemorrhage of the two died, and other died Massive MI. There was no post operative new deficits seen. CT guided Stereotactic biopsy is a very effective and low cost procedure caomparing with frameless image guided brain biopsies or open craniotomy for biopsy due to it’s higher complication rate. The detail procedure are being discussedBang. J Neurosurgery 2020; 9(2): 86-93